Socio-Cultural and Economic Challenges of Remarriage for Elderly Widows and Widowers in Nepal - Dahal, Anita (Academia Journal of Humanities & Social Sciences, 2025)
Elderly widows and widowers in Nepal are often advised to refrain from remarrying due to social stigma and financial hardships caused by cultural beliefs and financial reliance. These barriers limit their freedom, which affect their general well-being and social inclusion. In these regards, this study aimed to explore the barriers to remarriage among elderly widows and widowers in Nepal, focusing on cultural, economic, emotional, and family factors together with examining the societal attitudes toward the elderly people’s remarriage and analyzing the perceptions of older adults on this issue. This study has employed an explanatory sequential mixed-method approach. Similarly, the quantitative data were used to explore the perception of them and the qualitative data were used to study in depth through the open ended questionnaire to support the quantitative findings. Sample was selected through the purposive and snowball sampling method. Data were statistically analyzed by using cross tabulation, frequency distribution, and descriptive statistics. Case studies were analyzed to find their alignment with the qualitative data findings. The findings of the study highlighted the significant barriers to remarriage, including social stigma, financial instability, lack of family support, and emotional attachment to the late spouse’s family. A fear of societal criticism appeared as the leading societal discouragement factor. Further, widows, in particular, faced cultural and family challenges, contrasts to widowers who encountered fewer barriers. Although remarriage can improve emotional health and lessen loneliness, older persons are discouraged from doing so by family restriction, financial concerns, and social stigma. Cultural changes and awareness-raising initiatives are crucial to improving the quality of life for elderly widows and widowers in Nepal and normalizing remarriage.